2016
DOI: 10.1017/s1368980016001385
|View full text |Cite
|
Sign up to set email alerts
|

Fast-food exposure around schools in urban Adelaide

Abstract: Disadvantaged schools were exposed to more fast food, with more than twice the number of disadvantaged schools exposed to fast food. The higher exposure to fast food near more disadvantaged schools may reflect lower commercial land cost in low-SES areas, potentially creating more financially desirable investments for fast-food developers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Thirteen studies examined access to food outlet types, 12 by area‐level SEP and 1 study examined access to food outlet types and how this varied using an individual measure of education as a proxy for SEP . Eight studies found significant associations in the hypothesized direction; that is, more disadvantaged areas had significantly more unhealthy food retail environments; four studies reported mixed findings; one study reporting non‐significant results …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies examined access to food outlet types, 12 by area‐level SEP and 1 study examined access to food outlet types and how this varied using an individual measure of education as a proxy for SEP . Eight studies found significant associations in the hypothesized direction; that is, more disadvantaged areas had significantly more unhealthy food retail environments; four studies reported mixed findings; one study reporting non‐significant results …”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined children's food retail environments examining food sources around children's homes and en route to school by area‐level SEP, two studies examining food sources in geographic units containing schools . One study undertook an analysis of vending at train stations across area‐level measures of SEP reporting that mean numbers of items in vending machines at train stations was higher in high‐SEP areas, whilst the mean number for healthy items was higher in mid‐SEP and high‐SEP areas …”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study have important implications for future research, but policymakers in public health, land use planners and others interested in creating healthy environments should interpret the results of this study with caution. First, children attending schools in neighbourhoods of deprivation in Australia and NZ are significantly more likely than their peers in more privileged neighbourhoods to be exposed to unhealthy food outlets 11 35. However, the direct connection between increased exposure to these food outlets and unhealthy dietary behaviours of children has not yet been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Businesses selling unhealthy food and drinks target children,8 population groups on low incomes and those living and working in deprived neighbourhoods 9. In NZ and other high-income countries, unhealthy food outlets such as fast-food or takeaway restaurants and convenience stores that sell predominately energy dense, nutrient poor foods and beverages10 are more likely to be found in highly deprived neighbourhoods 11–13. Moreover, food purchasing behaviour is important to consider as systematic reviews show associations between eating out of home and higher overall energy intake14 and poorer overall diet quality 15.…”
Section: Introductionmentioning
confidence: 99%
“…As much as 31% of the variance in excessive fast-food consumption may be attributable to simply living in urban areas with moderate or high density of fast-food outlets [302]. On our walk we will surely encounter greater clustering of fast-food outlets and convenience stores around schools, as seen in numerous international studies [303,304,305,306,307,308]. We will find much higher brand name logo recognition in children in lower SES neighbourhoods [309].…”
Section: Behavioral Reinforcementmentioning
confidence: 99%